Bioestimulante e fertilizantes foliares no cultivo de Brachiaria híbrida - Lima, Luara Cistina de (2016)
Bioestimulants provide increments in plant development when applied alone or in combination with other products. However, few studies address aspects vegetative and productive, related to the application of these in forage grasses. In addition, the objective of this work was to study the responses of grasses, submitted the application of bioestimulants and fertilization. It was installed two experiments, using the Brachiaria hybrid Convert HD364, on the Capim Branco Farm, belonging to the Federal University of Uberlândia. The first experiment was conducted in randomized blocks with six treatments and four replications. The treatments were doses of biostimulation (0.25; 0.5; 0.75; 1.00 and 1.25 L ha-1 in each application) and the witness who appeared to be the lack of application of bioestimulant. The second experiment was conducted in a completely randomized block design, with seven treatments and three replications. The treatments were: control (absence of fertilization), application of 30 kg ha-1 N (urea); 30 kg ha-1 N (urea) + 3.0 L ha-1 of Mastermins® Pasture; 30 kg ha-1 N (urea) + 3.0 L ha-1 of Starter®; 30 kg ha-1 N (urea) + 0.5 L ha-1 bioestimulant; 30 kg ha-1 N (urea) + 3.0 L ha-1 of Mastermins® Pasture + 0.5 L ha-1 bioestimulant; 30 kg ha-1 N (urea) + 3.0 L ha-1 of Starter® + 0.5 L ha-1 of bioestimulant, applied in each cycle, after the cut. The evaluations were forage production, nutritive value (CP, NDF and ADF), and root mass and leaf analysis for nutrient content. There was a regression testing for the first experiment and the Tukey test at 0.05 significance for the second experiment. For the first experiment, concluded that the bioestimulant promotes an increase in the accumulation of MS and the rate of accumulation of grass, leaves and stems of Brachiaria hybrid, a reduction in the percentage of dead material and in relation to F:C Brachiaria hybrid and does not interfere in the contents of N, K, P, Ca, Mg, S, B, Cu, Fe, Mn and Zn, the accumulation of K, P, Ca, Mg, S, B, Cu, Fe, Mn and Zn, the accumulation of MS and the rate of accumulation of dead material, the density of roots, and percentage of leaf and the concentrations of ADF, NDF and PB, from the results it is recommended that the dose of 1.25 L ha-1 bioestimulant for Brachiaria hybrid, Convert HD364. For the second experiment, concluded that Starter N® associated with the bioestimulant and urea promotes greater accumulation of MS of forage. Starter N® associated with urea, Mastermins Pastureland® associated with urea and biostimulating and Starter N® associated with urea and the bioestimulant promote increases in accumulation of MS from leaves and stems. Starter® associated with urea, Mastermins Pastureland® associated with urea, Mastermins Pastureland® associated with urea and the bioestimulant and Starter® associated with urea and the bioestimulant promotes an increase in the accumulation of MS of dead material. Mastermins Pastureland® associated with urea and the bioestimulant and Starter® associated with urea and the bioestimulant promotes an increase in the rate of accumulation of leaf. Starter® associated with urea, Mastermins Pastureland® associated with urea and the bioestimulant and Starter® associated with urea and the bioestimulant promotes increased rate of accumulation of stalk rot.